A short review of contemporary developments in aquatic ecosystem modelling of lakes and reservoirs. (July 2019) - Frassl, Marieke A.; Abell, Jonathan M.; Botelho, Daniel A.; Cinque, Kathy; Gibbes, Badin R.; Jöhnk, Klaus D.; Muraoka, Kohji; Robson, Barbara J.; Wolski, Malcolm; Xiao, Man; Hamilton, David P.
Highlights: Concise review of the recent advances in numerical modelling of lakes and reservoirs. Coverage of model development, modelling methods and socio-economic perspectives. Discussion of ways forward for the aquatic ecosystem modelling community.